Managing the Professional Practice : In the Built Environment - Smyth, Hedley (Hoboken : John Wiley & Sons, 2011)
The emphasis here is to explore the key issues influencing the culture, strategies and management operations of professional practices. The focus is upon established practices from growing ones to large international firms in the built environment. A key aim of the book is to promote aspects of management by function and activities, with discipline acting as context rather than the primary focus. The book is structured into sections around 3 main themes: managing the organisation; and managing specific issues that affect operations, and a third section reflects upon management from practitioner.
Chapter 11: Squaring the circle: Delivering international services locallyChapter 12: Innovation in the construction sector; Chapter 13: Managing a project management division; Chapter 14: Developing capacity in an emergent market; Chapter 15: Branding professional services: Making the intangible tangible; Chapter 16: The first 20 years; Chapter 17: Reflection on the redevelopment of the University of Tokyo Hospital: The last 26 years; Chapter 18: Beyond the first generation; Chapter 19: Changes in UK construction professional services firms in the late 20th century; Conclusion; Acronyms.
Includes bibliographical references and index.
Print version record.
Keywords: Construction industry -- Management; Engineering; Architecture; Business; Civil engineering; Construction industry -- Management; Electronic books